The Effect of Perceived Usefulness and Pereceived Ease of Use on Trust and Repeat Purchase Interest in Omnichannel Retailling - Utaminingsih, Fitriana; Sumiyati (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study aims to determine the influence of perceived usefulness and perceived ease of use on trust and repurchase interest in Omnichannel Retailling. This research is an associative research. The population in this study is active students of the Faculty of Economics and Business, University of Muhammadiyah Pontianak for the 2023/2024 academic year. The number of samples was 120 respondents determined by purposive sampling technique. The data analysis technique used is structural equation modeling (SEM) with SmartPLS 4. The results of hypothesis testing for direct influence showed that Perceived Usefulness had a positive and significant effect on Trust, Perceived Ease of Use had a positive and significant effect on Trust, Perceived Usefulness had a positive and insignificant effect on Repurchase Interest, and Perceived Ease of Use had a positive and significant effect on Repurchase Interest. The results of hypothesis testing for indirect influence show that Perceived Usefulness has a positive and insignificant effect on Buyback Interest through Trust, Perceived Ease of Use has a positive and insignificant effect on Buyback Interest through Trust